2012
DOI: 10.1109/tasc.2011.2176455
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Quench Protection System for a Coated Conductor Insert Coil

Abstract: Coated conductors are promising material for the construction of high field magnets, but the slow propagation velocity of the normal zone makes the protection against quenches a critical issue. The quench protection system for a small insert coil under development at CRPP has been studied. The voltage drop and the hot spot temperature during the quench have been estimated using analytical expressions; the cross section of the copper stabilizer, the voltage threshold and the time constant were set as parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…One obvious step that may be undertaken is to increase the thickness of the metal stabilizer in order to be able to reduce the rate of heating at the developing hot spot. The effectiveness of this approach is demonstrated, for example, in [97], where the increase of the copper stabilizer cross-section in the ReBCO conductor from 0.16 mm 2 to 0.4 mm 2 yielded a two times reduction of the hot spot temperature in the current dump experiment on an HTS insert coil. An obvious drawback of this approach, however, is that the proportionally reduced engineering current density of the conductor reduces the magnet performance.…”
Section: Conductor Modificationmentioning
confidence: 99%
“…One obvious step that may be undertaken is to increase the thickness of the metal stabilizer in order to be able to reduce the rate of heating at the developing hot spot. The effectiveness of this approach is demonstrated, for example, in [97], where the increase of the copper stabilizer cross-section in the ReBCO conductor from 0.16 mm 2 to 0.4 mm 2 yielded a two times reduction of the hot spot temperature in the current dump experiment on an HTS insert coil. An obvious drawback of this approach, however, is that the proportionally reduced engineering current density of the conductor reduces the magnet performance.…”
Section: Conductor Modificationmentioning
confidence: 99%
“…Ishiyama et al, worked out general equations to estimate the optimal stabilizer cross-section for a SMES magnet operated at 50 K [133]. Regarding high-field coils, simulation study by Uglietti and Marinucci has shown that a moderate increase in copper cross-section coupled with a sensitive quench detection and a short discharge time constant are sufficient to passively protect a 4 T/40 mm bore magnet [134]. For large coils the copper cross-section should be further increased if a passive protection system (shunt resistors with diodes) is used.…”
Section: Quench Protectionmentioning
confidence: 99%
“…It has been shown in Ref. [25] that increasing the stabilizer thickness aids in reducing the magnet temperature at a quench. For the AMS-100 magnets, we assume that the copper stabilizer will be replaced by an equivalent aluminum stabilizer to minimize the material budget [26].…”
Section: Ams-100 Magnet Systemmentioning
confidence: 98%